Development and Evaluation of a Shared Decision‐Making Patient Decision Aid for Dental Clinic Care: A Mixed‐Methods Study - Ching‐Wen Liu; Hsiao‐Hui Jung (Health Science Reports, 2026)
ABSTRACT Background and Aims Shared decision‐making (SDM) is increasingly recognized as a core element of patient‐centered dental care, promoting collaboration between clinicians and patients to ensure that treatment decisions reflect both clinical evidence and individual preferences. However, few patient decision aids (PDAs) tailored to dental contexts have been systematically developed or evaluated. This study aimed to develop a dental‐specific PDA and explore patients’ perceptions of SDM following PDA‐assisted consultations. Methods A mixed‐methods design was employed in Taiwan, combining a quantitative survey ( n = 46) using the 9‐item Shared Decision‐Making Questionnaire (SDM‐Q‐9) and qualitative focus group interviews ( n = 11). Quantitative analyses included t ‐tests and ANOVA to examine demographic and treatment‐related variations, while qualitative data were analyzed using thematic analysis with open, axial, and selective coding procedures derived from grounded theory approaches. Results Patients reported high overall SDM‐Q‐9 scores ( M = 5.88, SD = 0.27; however, this mean approaches the scale maximum of 6.0, suggesting a potential ceiling effect that may have limited score discrimination). Significant variations were observed by gender ( p < 0.05), marital status ( p < 0.001), and treatment type ( p < 0.05), suggesting that demographic and clinical contexts were associated with differences in perceived SDM. Focus group findings identified three modes of participation: tool‐driven, passive acceptance, and integrative reflective participation. Patients emphasized the importance of clear communication, supportive provider interaction, and contextual readiness in shaping their decision‐making experiences. Conclusion Patients reported high levels of perceived SDM following PDA‐assisted consultations, and qualitative findings suggested that the PDA was viewed positively as a tool to support communication and treatment discussions. The study contributes theoretically by extending transformative learning theory into dental decision‐making, practically by providing tailored strategies for PDA deployment, and at the policy level by highlighting dentistry as a favorable setting for SDM implementation due to its multi‐visit treatment structure.